ChemInform Abstract: A Novel, High‐Yielding Approach to a Chiral Inducer: (2R, 3R)‐1, 4‐Dimethoxy‐1, 1, 4, 4‐tetraphenylbutane‐2, 3‐diol. Issue 40 (30th September 2014) - Hu, Xiaoyun; Shan, Zixing; Song, Shaojun
Abstract The improved synthesis of the title species (IV) involves the selective 2, 3‐spiroboration of substrate (I) as key step followed by methylation and hydrolyzation.